Nel «melograno di lingue» Plurilinguismo e traduzione in Andrea Zanzotto - Bongiorno, Giorgia; Toppan, Laura (Moderna/Comparata, 2018)
This book was born from an observation and a desire. The starting point is that the multilingual nature of Andrea Zanzotto's poetry becomes almost invisible by virtue of being evident in the eyes of its readers. The babelic hypersensitivity of the petèl's poet is certainly not absent in critical studies, yet this work addresses it in a systematic way for the first time, by investigating on the multiple connections between poetic writing and languages. The desire that accompanied this reflection was to lead it with a "prismatic" gaze, crossing the poetry's multilingualism and the poet's translation practice, and summoning the many voices of its translators around the Zanzottian multivocality. A series of unpublished documents in the appendix, and the interventions of poets like Cecchinel, Demarcq and Rueff, alongside those of the best European experts of Zanzotto, add a special significance to this work. Speech given on June 26, 2007 at the Locanda da Lino in Solighetto (TV, Italy) on the occasion of the presentation of the book by F. Carbognin, L'«altro spazio». Scienza, paesaggio, corpo nella poesia di Andrea Zanzotto (Nuova Editrice Magenta, 2007) and of issue no. 230 of «l'immaginazione» (year XXII, May 2007). Videotaped and included in the DVD Tribute to Andrea Zanzotto (Viviafilm production), which also includes speeches by Niva Lorenzini, Marco Antonio Bazzocchi and Silvana Tamiozzo Goldmann.